A power balance model for handcycling - Groen, W. G.; van der Woude, L. H. V.; de Koning, J. J. (Disability and Rehabilitation, 2010)
Purpose. To demonstrate the applicability of the power balance model to elite handcycling and to obtain values for gross efficiency (GE).